PENGGABUNGAN PASAR GULA KONSUMSI LANGSUNG DENGAN PASAR GULA INDUSTRI - Wayan R. Susila; Ernawati Munadi (School of Business, Bogor Agricultural University (SB-IPB), 2007)
The government policy to separate the sugar market for direct consumption from industrial use has raised conflicts between sugar producers in both markets. This is due to the fact that the sugar in the industrial use market enters the market of sugar direct consumption, vice versa. To overcome this conflict, merging both markets as adopted in most countries is a potential policy option. This study aims to asses the magnitude and distribution of the impact of merging the markets. The results of the analysis showed that the impacts will strongly be influnced by the price of the sugar in the international market. When the price is low (US 300/ton), the producers of sugar direct consumption (faremers and sugar white sugar plants) will suffer from the merger, while refine sugar producers and consumers will gain benefits. However, as a whole the merger will create a net surplus around Rp 560 Billion. The reverse will occur if the merger is implemented when the sugar price is high (US 350/ton). As a whole, the merger will cause welfare lose of around Rp 1500 Billion. To overcome the negative impacts of the mergers, some policies options are also proposed in this study